Human T-Lymphotropic Virus, Associated Myelopathy and Leukemia: A Review - Auwal, I. Kabuga; Lawal D. Rogo (UMYU Journal of Microbiology Research)
Human T Lymphotronic Virus type 1 was the first retrovirus discovered associated with fatal diseases in humans and said to have emerged following zoonotic transmission from simian populations. Their primary target is adult CD4 T-cells and most infected individuals are asymptomatic. However, a significant number may develop persistent infection and progress to an aggressive lymphoproliferative disease, known as Adult T-cell Leukemia/Lymphoma-ATLL. Some may develop a debilitating neuro-inflammatory disease called Tropical Spastic Paraparesis-TSP, predominantly involving the lower limbs, with or without hyperactive urinary bladder. Unprotected sexual intercourse and breastfeeding account for the highest number of cases and is also transmitted by uncheck blood transfusion or sharing of contaminated sharps. ATLL and TSP are life-threatening diseases initially restricted to Middle East and some parts of Africa, but recently, cases are being reported in many parts of the world. Unfortunately, even though the antiretroviral therapy have greatly improved and significantly reduced HIV progression to AIDS, such great break through is not worthy benefit for HTLV infected individuals. Thus, they are identified as severe human diseases of public health concern. This review is an overview and contains update about the biology of the virus, its interaction with the host, HAM/TSP and ATLL; their epidemiology and clinical presentations.